Predicting and mapping the location of an estimated population from a survey: an applied method - Philippe Gerber (Unité Mixte de Recherche 8504 Géographie-cités, 2010)
On the basis of a survey conducted with elderly in the city of Luxembourg (N = 903) in 2002, this text presents a method aiming to predict the localisation of an estimated population liable to health relevant problematics. The main objective of this methodology is to aggregate individual information (point mapping) to produce discrete information (area mapping). This dimensional change is obtained by a projection procedure. This projection makes possible the mapping of the characteristics observed in the survey, at a fine scale and for the entire city.